Faktor - faktor yang Mempengaruhi Manajemen Laba Perusahaan - Nanda Ayu Cahyaning Thyas (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
Abstract : This study aims to determine and analyze the effect of leverage, firm size, free cash flow, and operating cash flow on the earnings management of the food and beverage subsector companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The population in this study were 26 companies. The technique of determining the sample using purposive sampling technique, so that the final sample obtained was 12 companies. The data used are secondary data obtained from the financial statements of the food and beverage sub-sector companies listed on the Stock Exchange in the 2015-2018 period. The data analysis technique used is the classic assumption test and multiple linear regression analysis with the help of the application SPS version 21. Based on the results of the study showed that leverage, free cash flow, and operating cash flow have no effect on earnings management, while firm size affects earnings management.